International standards and tools for management of innovative projects in construction - Gorbach, M.V.; Dubensky, O.M.; Chernenko, M.E.; Ostapenko, I.I.; Funtikov, V.O. (Ways to Improve Construction Efficiency, 2023)
In the context of globalization and digital transformation of the industry, there is a growing need to integrate generally recognized standards, such as ISO 21500, PMBOK, PRINCE2 and others, which provide a unified approach to project management. These standards define the basic principles of planning, monitoring, control and performance evaluation, which are critically important for the successful implementation of innovative solutions in complex construction projects. Particular attention is paid to digital management tools based on the use of information technologies, such as BIM, CAD and specialized software for resource planning. The integration of these tools allows you to create a comprehensive information model of the project, which provides accurate visualization, automation of calculations and coordination of actions between various participants in the process. The use of such tools increases the accuracy of risk assessment, optimizes decision-making processes and helps minimize costs and time for completing tasks. International practice shows that the implementation of innovative approaches in construction requires the adaptation of existing standards to specific market conditions, as well as the development of national recommendations that take into account legal, economic and social aspects. Knowledge management occupies a special place, because the successful implementation of projects depends on the effective exchange of experience, the creation of knowledge bases and the application of modern methods of training specialists. In this context, analytics and forecasting tools play an important role, providing accurate data for assessing the feasibility of implementing innovations. In particular, machine learning and artificial intelligence technologies open up new opportunities for analyzing large amounts of information and automating decision-making processes. In addition, strategic management focused on sustainable development contributes to increased environmental responsibility and the implementation of energy-efficient solutions. Thus, international standards and tools for managing innovative projects in construction are an important factor in the development of the industry. Their implementation ensures increased efficiency, integration of advanced technologies and harmonization of management approaches, contributing to the formation of competitive and sustainable construction practices.